Accuracy of 2 Different Continuous Glucose Monitoring Systems in Patients Undergoing Cardiac Surgery: Intravascular Microdialysis Versus Subcutaneous Tissue Monitoring. (January 2017) - Schierenbeck, Fanny; Franco-Cereceda, Anders; Liska, Jan
Background: Continuous glucose monitoring (CGM) is today provided by various techniques. This study aims to compare two different CGM-systems: the FreeStyle Libre subcutaneous continuous glucose monitoring system (SC-CGM) and the Eirus intravascular microdialysis continuous glucose monitoring system (MD-CGM) in patients undergoing cardiac surgery. Methods: A total of 26 patients were equipped with both the SC-CGM and the MD-CGM systems. The SC-CGM system was placed subcutaneously in the left upper-arm and the MD-CGM system was placed in the superior vena cava. Reference blood glucose values were obtained by analyzing arterial blood in a blood gas analyzer. Reference glucose values were then paired with glucose values from both CGM-systems and analyzed for accuracy. Results: In all, 514 paired MD-CGM/arterial blood gas glucose values and 578 paired SC-CGM/arterial blood gas glucose values were obtained. Mean difference (SD) for the MD-CGM system was 0.9 (15.1) mg/dl and for the SC-CGM system −43.4 (20) mg/dl. ISO criteria (ISO15197:2013) were not met by either CGM system. In the Clarke error grid, all paired samples were within the zones AB for the MD-CGM system, and 94% in zone A. For the SC-CGM system, 99.1% of the paired samples were within zones AB, and 18.9% in zone A. Both the MD-CGM and the SC-CGM systems were reliable and used without complications. Conclusions: These results indicate that the Eirus intravascular microdialysis system monitors glucose continuously with superior accuracy compared to the FreeStyle Libre subcutaneous glucose monitoring system, which repeatedly measured a glucose value that was lower than the reference method.